A conceptual framework of sustainable development strategy as "corporate responsibility" in manufacturing industry. Issue 3 (8th June 2018) - Sulistiarini, Emma Budi; Suparman, Sudjito; Santoso, Purnomo Budi; Tama, Ishardita Pambudi
Abstract: Previous studies have mentioned that there are market‐oriented corporate responsibility strategies, stakeholder‐oriented corporate responsibility strategies, and sustainable development‐oriented corporate responsibility strategies. Those strategies are in the form of corporate responsibility to the people, to the planet, and to profit (widely known as the triple bottom line). The very crucial challenge faced by the manufacturing industry today involves environmental degradation and depletion of natural resources, both of which can be overcome by implementing sustainable development‐oriented strategies. In this study, data were obtained from sampling three manufacturing industry companies in East Java, Indonesia. The respondents selected for the survey included top management and employees. From the results of the survey review and descriptive analysis, the researchers created a framework of the concept of sustainable development as corporate responsibility for the manufacturing industry. There are three steps in the methodology: strategic thinking, model arrangement, and variable definition. Arranging the model itself also involves three steps, identifying: "what is the problem, " "boundaries, " and "components." The strategy model is in the form of a conceptual framework and strategy map, which are easily adapted as a guideline for the manufacturing industry. The model was tested using the Conceptual Framework for Strategic Sustainable Development and General Structural Component Analysis statistics. The conceptual model in this work used the five perspectives of responsibility applied within the manufacturing industry, which address the environment, social welfare, the intrinsic value of direct financial gain (in this context, this refers to competitive advantage), technology development, and performance management. Further research is needed to break down the conceptual framework and strategy map into more detailed, technical guidance.